Using Structural Equation Modeling for Assessing the Factors Affecting Gasohol 91 Consumption on the Personal Car - Kunlawong, Chainikorn (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2018)
The objective of this study was to assess the factors affecting gasohol 91 consumption of the personal car. The Structural Equation Modeling (SEM) is the statistical technique that is utilized to analyze the data. The data were obtained from the amount of the 558 personal car users in Muang District, Nakhon Ratchasima Province, utilizing the questionnaire as a tool to collect the data. The results of the final SEM indicated that the overall model is consistent with the empirical data. The most influential factor in the consumption of gasohol 91 on a personal car was the product, followed by the place, information search and pre-purchase evaluation of alternatives, post-purchase, price, promotion, purchase decision, problem recognition, and repair-maintenance, respectively. All influential factors could explain variation in gasohol 91 consumption by 83.20%.